Steering the AI world: an exploratory comparison of AI Acts in the EU and Canada - Ruiyi Zhu; Tien-I Tsai (Information Research: An International Electronic Journal)
Introduction. As artificial intelligence (AI) continues to grow rapidly, governments are implementing legislative frameworks to address its risks and opportunities. This paper provides a comparative analysis of AI Acts in the European Union (EU) and Canada, focusing on two legislative efforts: the EU artificial intelligence act (EU AI Act) and Canada’s artificial intelligence and data act (AIDA).